The Toba Batak tribe's cultural capital in the context of protecting Lake Toba from environmental threats - Lumbanbatu, Herbert A (Journal of Socio-Cultural Sustainability and Resilience, 2025)
Background: The Batak Toba tribe predominantly inhabits the Lake Toba area. Lake Toba and the Batak Toba tribe have a strong, unchangeable connection. The historically valued traditions of the Batak Toba tribe have developed over generations due to their interactions with Lake Toba, although they now face the threat of obsolescence and discord. Ecosystem services and tourism attractions are mostly utilized for economic purposes, lacking regard for local wisdom or cultural significance. Consequently, various degradations and environmental damages are inflicted by human activities and company operations in the Lake Toba area. This study aims to explore and provide the distinct cultural values of the Batak Toba tribe to promote the future sustainability of Lake Toba's ecosystem services, including protection against environmental threats and degradation. Methods: The employed methodology involved literature research and content analysis, augmented with videos obtained from diverse YouTube channels. Findings: The cultural values of the Batak Toba tribe that foster the sustainability of Lake Toba's ecosystem services encompass aek do hangoluan, poda na lima, marsirimpa, mambongoti bagas, and numerous Batak Toba songs pertaining to Lake Toba, including O Tao Toba, Tano Toba, Tao Toba Nauli, HORAS!, and Pulo Samosir. The abundance and diversity of these cultural values are expected to provide knowledge, enhance awareness among future generations of the Batak Toba tribe, and motivate a culture-driven environmental restoration initiative focused on restoring and preserving the ecological services of Lake Toba. Conclusions: The study provides a significant ecological and cultural connection between the Batak Toba tribe and Lake Toba, dating back to the era of their ancestors. Consequently, it shall remain inseparable. Novelty/Originality of this article:  The novelty of this research lies in the exploration of Toba Batak cultural values as a local wisdom-based approach to maintaining the sustainability of Lake Toba ecosystem services.